Estudo da internalização de macromoléculas em eritrócitos infectados pelo Plasmodium falciparum - Maluf, Sarah El Chamy [UNIFESP] (2019)
The intraerythrocytic development of the malaria parasite Plasmodium falciparum is dependent on the uptake of essential nutrients from the host cell cytoplasm and blood plasma. It is widely recognized that it imports low molecular mass nutrients, such as polyols, amino acids, lipids, nucleosides, organic anions and cations from the plasma. However, although some studies show that P. falciparum is capable of importing macromolecules from the host, the route for internalization continues to be subject of debate between different groups, mainly due to the necessity of these macromolecules to pass through three membranes, namely the erythrocyte, parasitophorous vacuole and the parasite membrane itself. To better understand this process, this study provides new evidence to help elucidate the mechanism used by the parasite to internalize macromolecules with a focus on protein uptake. Using different experimentais approaches, we demonstrated that P. falciparum imports human plasminogen and the exogenous protein crotamine, at different stages of its intraeritrocitic development. In the infected erythrocyte, plasminogen is located in the parasite's cytosol, and is also present in the Maurer’s Cleft and tubular structures in the erythrocyte cytosol, which are described as being associated with the export of proteins. In addition, some interactions may be involved with the internalization of plasminogen, such as with Rabs proteins, kinesin, myosin, PfMC-2TM, Pf113 and heat shock proteins. There was a significant decrease in the uptake of plasminogen by the parasites after cytochalasin D treatment, suggesting a participation of the actin-myosin motor system in protein trafficking. Crotamine was selectively internalized by infected erythrocytes, and presented a colocalization with the parasite nucleus and part of the protein remains associated with the erythrocyte plasma membrane. The uptake was 2-deoxy-D-glucose sensitive, indicating that it is a mechanism dependent on energy via glycolysis. The results obtained here offer new elements involved in macromolecular uptake pathways in infected erythrocytes, which may constitute a potential target for the development of new drugs, in addition to identifying the permeability characteristics of the infected cell.